Electronic design : circuits and systems - Savant, C. J., Jr. (California : Benjamin Cummings, 1991)
This book is written for use in the core electronics courses an undergraduate programs in electrical engineering. The book provides coverage of three area: discrete devices, linear integrated circuits, and digital integrated circuits. A practicing engineer looking for a current reference for self-study will also find this book valuable.
Keywords: ELECTRONIC CIRCUIT DESIGN